Menumbuhkan Semangat Nasionalisme Melalui Penguatan Pemahaman Karya Sastra: Pengabdian - Sirilus Karolus Keroponama Keban; Yoakim Yolanda Mario Leu; Pilipus Wai Lawet; Rikardus Pande; Vinsesius Crispinus Lemba; Imelda Oliva Wissang; Gregorius Tuli Aran; Rikarno Bana; Maria Antonela Ona G. Kleden (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This service article aims to describe the spirit of nationalism in young people that is fostered through strengthening the understanding of literary works. Through literary activities or activities, it can be found that literary works have a role (1) as a container for value education and character formation, (2) as a source of innovation to produce new works that answer the challenges of the times, such as writing poetry, short stories, novels, literary essays to literary studies, (3) a container for control and critical thinking towards situations, realities of life, and (4) a source of self-improvement, such as intelligence, competence, skills, professionalism.